Feasibility and safety of remdesivir in SARS‐CoV2 infected renal transplant recipients: A retrospective cohort from a developing nation. Issue 4 (18th May 2021) - Meshram, Hari S.; Kute, Vivek B.; Patel, Himanshu; Banerjee, Subho; Navadiya, Vijay; Desai, Sudeep; Rizvi, Syed J; Mishra, Vineet; Chauhan, Sanshriti
Abstract: Introduction: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV2) infection has drastically impacted the transplant communities. Remdesivir (RDV) has shown some promising results in coronavirus disease (COVID‐19) albeit with low certainty. Data in kidney transplant recipients (KTR) are still lacking. Methods: This was a retrospective cohort of 57 moderate to severe COVID‐19 positive KTR in a single center who received RDV as a part of COVID‐19 management. No dose adjustments were done. The outcomes were measured as acute kidney injury (AKI) recovery; liver function tests abnormalities; other side effects; graft loss and death. Results: The median (inter‐quartile range) age of presentation was 44 (31‐51) years. The duration from onset of symptoms to RDV initiation was 6 (5‐7) days. Thirty‐two (56%) cases received RDV on the day of admission. Forty‐six (81%) cases were on oxygen support upon initiation of RDV. Thirty‐eight (66.6%) cases had acute kidney injury on admission. The median baseline, admission, and 28‐day follow‐up serum creatinine of the cohort were 1.59 (1.1‐2.1), 2.13 (1.3‐3.1), and 1.58 (1.05‐2.1) mg/dl, respectively. A total of 8(14%) cases died in the study with 1 (1.7%) graft loss. All those cases that died were on oxygen therapy at the time of initiation of RDV. No liver function derangements or any other major adverse events with the drug were reported. Conclusion: RDV therapy is safe and clinically feasible in renal transplant recipients as seen in our cohort. Larger clinical registries and randomized clinical trials should be conducted to further explore the efficacy in transplant recipients.